Crystallisation of Ionic Liquidby Using Avrami Kinetic Theory - Ishak, Muhammad 'Imran (Universiti Teknologi PETRONAS, 2012)
Ionic liquids have received an immense increase in interest in the fields of engineering during the last decade due to their distinctive properties. Ionic liquids (ILs) are molten salts having by definition melting points below 100DC and a very important new class of non-volatile environmentally friendly solvents as compared to traditional organic solvents. This study is focused on crystallisation of ionic liquid which is one of the possible techniques to purify ionic liquids. Different factors that influencing will be explored such as: effects of temperature variations, effects of cooling rate, effects of seeding procedure (addition of crystals as solid) and effects of ionic liquid content. Analyses will be conducted to evaluate and characterize the ionic liquid crystallisation are: the percentage of ionic liquid crystallisation (S, wt.%); the Avrami exponent (n) which correspond to the type of crystals; and the half time of crystallisation (tm) which is associated with the rate of crystallisation. On the study of the effect of temperature deviations, it was found that increasing the initial temperature (T\) reduced the overall crystallisation; increase of the initial temperature (Ti) altered the type of ionic liquid crystal from needle type to clustered plate-like shapes; and decreased the rates of crystallisation. On the effect of cooling rate, it was observed that decreasing the cooling rate reduced the crystallisation, increased n and t\n values hence reduced the crystallisation rates. The study on the effect of seeding procedure revealed that crystallisation increased with seeding procedure, increased n value, decreased tm and caused lower crystallisation rate. Lastly in the effect of ionic liquid content, it was found that the higher the ionic liquid content, the longer times were taken to produce ionic liquid crystals, increased n and t\n. Since the use of ionic liquid in industrial applications is relatively a new technology, perhaps the results of this study will provide useful information for understanding of the crystallisation behaviour of this new class of materials.